Remoção de microcistina-LR através de adsorção com carvão ativado - Lima, Natassya Nyuska Cabral de (2015)
The occurrence of cyanobacterial blooms in water sources used for public supply, is increasingly common. Some genera of cyanobacterial have species potentially producing cyanotoxins, which can affect human health by direct contact through the skin or by ingestion of contaminated water or food. Classified according to their pharmacological action, cyanotoxins, are known as hepatotoxins, neurotoxins and dermatotoxins. Among the hepatotoxins we found the microcystin, a cyclic heptapeptide which can lead to death in hours or days. During the treatment of water for human consumption it is important to consider a technique to remove intact cells of cyanobacteria, since the use of oxidizing agents promotes cell lysis which can cause the release of toxins into the water. The Activated Carbon (AC) is presented as one of the best alternatives to the removal of organic and inorganic compounds due to its high power of adsorption. Aimed the fulfillment the current drinkability ordinance, as the concentration of extracellular cyanotoxins the present study sought to evaluate on a bench scale, the microcystin-LR removal efficiency study of water by adsorption on Activated Carbon (AC). The water study of was prepared with addition of lysed cells Microcystis aeruginosa cultivation. Were evaluated different pH values and the results confirmed that MC-LR adsorption was more efficient at acidic pH close to 5,0. Kinetic studies of adsorption were performed, analyzed according to the models of pseudo-first and pseudo-second order, getting the best fit the model of pseudo-first order, and adsorption isotherms to determine the adsorptive capacity of CA in relation to microcystins. The data of the isotherms were modeled according to the Langmuir isotherm and Freundlich, with best fit to the Langmuir model.The analytical method used during research to determine the concentration of microcystin-LR, after completion of kinetic experiments and isotherm was the High Performance Liquid Chromatography Coupled with Mass Spectrometry (HPLC-MS). The adsorption by AC palm coconut shell proved to be an efficient process for the removal of MC-LR, since averages toxin removal efficiencies above 90% were observed.